Legal Responsibility of Hospitals in Maintaining the Security and Confidentiality of Patients' Electronic Medical Record Data - Anthony Anugrah Jeshua; Anak Agung Ngurah Gede Anggra Pramana (Syntax Idea)
The very rapid development in health services today requires that every health service provider organize medical records electronically with the principles of security and confidentiality of data and information. However, in practice, Elecronic Medical Records is still experiencing many legal issues that are detrimental to both the Hospital and especially the patients themselves. Therefore this study aims to analyze the legal basis of hospital obligations for the security and confidentiality of electronic medical record patient data and analyze the responsibility of hospitals for the security and confidentiality of patient’s EMR data. The type of research used in this thesis is normative juridical research with statutory approach and conceptual approach. The results still found some legal wins, ambiguities and some shortcomings in implementing this EMR in full